THE UTILIZATION OF KINEMASTER APPLICATIONS IN THE MAKING OF MULTIMEDIA BASED TEACHING MATERIALS FOR ENGLISH E-LEARNING IN NEW NORMAL (COVID-19) - Haryudin, Acep; Imanullah, Farhan (PROJECT (Professional Journal of English Education), 2021)
The objectives of this study are; 1) to determine the ability in implementing online learning and multimedia use, 2) to determine the difficulties in online learning and difficulties in providing multimedia-based learning. 3. to assist participant in making multimedia-based learning media with the Kinemaster application. Researchers use descriptive qualitative methods. Respondents in this study were prospective students participating of English Education study program. 62.5% of respondents when teaching always use multimedia, 25% sometimes use multimedia in teaching, and 12.5% rarely use multimedia. Regarding difficulties in class management as much as 50%, in time management 25% and difficulties in operating software 25%. Other obstacles experienced are; 42.9% of the obstacles are networking, then 42.9% of the software application systems are not easy to operate and electrical energy sources 14.3%. The number of respondent 100% not only know but have also used the kinemaster application in making multimedia-based learning media by 62.5%, and 37.5% who never used the kinemaster, 62.5% of respondents said it was easy and 37.5% still had difficulties,. kinemaster really helps respondents in learning as much as 50% stated that they were helped, 12.5% did not feel helped, and 37.5% stated that it was normal. Keywords:  Kinemaster, Multimedia, English Online Learning